If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5z + -1) + -5(2 + 9) = 2(z + 1) Reorder the terms: 4(-1 + 5z) + -5(2 + 9) = 2(z + 1) (-1 * 4 + 5z * 4) + -5(2 + 9) = 2(z + 1) (-4 + 20z) + -5(2 + 9) = 2(z + 1) Combine like terms: 2 + 9 = 11 -4 + 20z + -5(11) = 2(z + 1) Multiply -5 * 11 -4 + 20z + -55 = 2(z + 1) Reorder the terms: -4 + -55 + 20z = 2(z + 1) Combine like terms: -4 + -55 = -59 -59 + 20z = 2(z + 1) Reorder the terms: -59 + 20z = 2(1 + z) -59 + 20z = (1 * 2 + z * 2) -59 + 20z = (2 + 2z) Solving -59 + 20z = 2 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -59 + 20z + -2z = 2 + 2z + -2z Combine like terms: 20z + -2z = 18z -59 + 18z = 2 + 2z + -2z Combine like terms: 2z + -2z = 0 -59 + 18z = 2 + 0 -59 + 18z = 2 Add '59' to each side of the equation. -59 + 59 + 18z = 2 + 59 Combine like terms: -59 + 59 = 0 0 + 18z = 2 + 59 18z = 2 + 59 Combine like terms: 2 + 59 = 61 18z = 61 Divide each side by '18'. z = 3.388888889 Simplifying z = 3.388888889
| 2*-4=o | | -2*-4=ourfgn | | sin(7x)=cos(7x) | | (2d^2-9d)-(-4d^2+20d+17)= | | 2x+(18-x)=11 | | 6(-2)=r+5r | | P(x)=(60x-0.3x^2)-(5x+13) | | 3x+1/3=3x-1/2 | | ln(16x)= | | 5x+14=2+7x | | -1(-1)=z | | 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= | | (x-4)2=(x-2)2 | | x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 | | x*x+4x+1=32 | | -12.1+0.5p=0.9+5.3 | | ln^5+ln(2x)=5 | | -[4(7)-(14(7)+8)]=8+(9(7)+7) | | 6+(-10)+(-2)+8= | | -12.1+.5=0.9p+5.3 | | -12+.5=0.9p+5.3 | | 3c+12=6c+11.31 | | 3c+12=6c+12.31 |